A remarkable group of thick‐headed Triassic Period archosauromorphs with a wide, possibly Pangean distribution. Issue 1 (3rd March 2021) - Nesbitt, Sterling J.; Stocker, Michelle R.; Chatterjee, Sankar; Horner, John R.; Goodwin, Mark B.
Abstract: The radiation of archosauromorph reptiles in the Triassic Period produced an unprecedented collection of diverse and disparate forms with a mix of varied ecologies and body sizes. Some of these forms were completely unique to the Triassic, whereas others were converged on by later members of Archosauromorpha. One of the most striking examples of this is with Triopticus primus, the early dome‐headed form later mimicked by pachycephalosaurid dinosaurs. Here we fully describe the cranial anatomy of Triopticus primus, but also recognize a second dome‐headed form from a Upper Triassic deposit in present‐day India. The new taxon, Kranosaura kuttyi gen. et sp. nov., is likely the sister taxon of Triopticus primus based on the presence of a greatly expanded skull roof with a deep dorsal opening (possibly the pineal opening) through the dome, similar cranial sculpturing, and a skull table that is expanded more posterior than the posterior extent of the basioccipital. However, the dome of Kranosaura kuttyi gen. et sp. nov. extends anterodorsally, unlike that of any other archosauromorph. Histological sections and computed tomographic reconstructions through the skull of Kranosaura kuttyi gen. et sp. nov. further reveal the uniqueness of the dome of these early archosauromorphs. Moreover, our integrated analysis further demonstrates that there are many ways to create a dome in Amniota. The presence of 'dome‐headed' archosauromorphs at two localities on the western and eastern portions of Pangea suggests that these archosauromorphs were widespread and are likely part of more assemblages than currently recognized. Abstract : Convergent evolution is repent in Triassic archosauromorphs and we highlight a Triassic acquisition of a pachyostotic cranial dome in Triopticus primus and a new, closely related taxon from the Triassic of India. We describe the external and internal morphology using detailed description, computed tomography, and histological sectioning.